An Observational Study of Lunchroom Interactions Among Secondary Students With Visual Impairments and Their Peers. (September 2022) - Travers, Hilary E.; Carter, Erik W.
Introduction: This study examined the naturally occurring social interactions of adolescents with visual impairments during lunch.Methods: We observed nine middle and high school students with visual impairments during multiple lunch periods (i.e., 44 total observations). We used interval recording (15 s observe, 15 s record) to collect data on our three primary variables: social interactions, social engagement, and proximity to others. We also took notes on quality of interaction (i.e., degree of reciprocity, appropriateness of content, affect of students and their peers, response relevance).Results: Students sat in close proximity to peers without disabilities for more than half of the observed lunch periods. However, students interacted with another person during only one-third of lunch periods. Interactions were more common with peers than with adults. Moreover, students without an additional cognitive impairment had higher quality and more frequent interactions with peers than adults; the opposite was true for students who had cognitive impairments in addition to visual impairments.Discussion: The findings of this study demonstrate that some students with visual impairments are very socially engaged during lunch, while others, namely those with additional cognitive impairments, have infrequent or low-quality interactions with peers during lunch.Implications for Practitioners: This study should prompt educators to consider the cafeteria as a context for supporting peer interaction and social skill development.